Mathematical Problem Solving Ability Based on KOLB Learning Style in Creative Problem-Solving Learning Models (Universitas Negeri Semarang, 2019)
The purpose of this study was to determine the quality of learning of the CPS learning model on the ability to solve math problems in fifth-grade students and describe the patterns of students' mathematical problem-solving abilities in terms of learning styles. This research is a qualitative descriptive study with the subject of fifth-grade students at Public Elementary School 1 Kalibawang, Wonosobo consisting of 18 students. The instruments used in this study were test and interview instruments. Data analysis includes reduction, presentation of data, and conclusion. The results showed the quality of learning with the CPS learning model on the ability to solve mathematical problems in both categories. It is shown with the results of the validation of proper learning tools, good quality learning, and the average score of students completing. Students with convergent learning styles can solve problems until the stage of re-checking, but at the stage of planning problem-solving lacks detail. Students with divergent learning styles can solve problems up to the stage of checking back, and can solve them well. Students with an assimilation learning style can solve problem until the re-checking stage, but at the planning stage of problem-solving are not perfect. Students with accommodation learning style can solve problem until re-checking stage, but at the stage of carrying out problem solving are not complete.